2012
DOI: 10.1039/c2jm31910a
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical porous carbon nanosheets and their favorable high-rate performance in lithium ion batteries

Abstract: Novel hierarchical porous carbon nanosheets (HPCS) with quantities of micropores and mesopores were prepared on a large-scale by using thermoplastic phenolic formaldehyde resin as the carbon source and copper nitrate as the template precursor. The HPCS, possessing a thickness of about 40 nm and the width of several microns, exhibited a high specific capacity and favorable high-rate performance when used as an anode material for lithium ion batteries (LIBs). The reversible capacities were 748 mA h g À1 at a cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
94
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 168 publications
(102 citation statements)
references
References 56 publications
7
94
1
Order By: Relevance
“…The charge-discharge curves rise and fall gradually without obvious voltage plateaus, revealing typical electrochemical characteristics of graphene flake carbon material, and the results agree well with the conclusions of other researchers [12]. The inset in Fig.…”
Section: Electrochemical Propertiessupporting
confidence: 91%
See 2 more Smart Citations
“…The charge-discharge curves rise and fall gradually without obvious voltage plateaus, revealing typical electrochemical characteristics of graphene flake carbon material, and the results agree well with the conclusions of other researchers [12]. The inset in Fig.…”
Section: Electrochemical Propertiessupporting
confidence: 91%
“…In contrast, the reduction peaks corresponding to the reversible extraction of lithium-ions extraction are gentle. The small reduction peak at 0.2 V observed in the charge process can be attributed to the extraction of lithium-ions from the graphite layers, and the peak at 1.3 V corresponds to the extraction from the cavities, which is similar to that of traditional mesoporous carbon [32] and porous carbon nanosheets [12]. The capacity below 0.5 V corresponds to the binding of lithium-ions on the surface of carbon layers and their intercalation into cavities, whereas the capacity above 0.5 V can be attributed to the faradic capacitance on the surface or on the edge sites of the re-CNSs [29,33].…”
Section: Electrochemical Propertiesmentioning
confidence: 80%
See 1 more Smart Citation
“…The spectroscopic and charge-discharge results demonstrated that the existence of wrinkles on re-CNSs can improve the initial specific capacity to 903 mAh g -1 . However, the low capacity retention rate of 4 approximately 44.3% after 100 cycles also indicated that there was a need to stabilize the capacity. Still, the unique structure and appearance of re-CNSs would not only facilitate coating them on the anode substrate of LIBs but would also improve their pileup density and electrochemical performances.…”
Section: Introductionmentioning
confidence: 90%
“…To date, several kinds of carbon nanomaterials, including flower-like nanosheets, hierarchical porous nanosheets, and hollow microspheres, have been reported to have higher capacities than the theoretical capacity of graphitic carbon [3][4][5]. Recently, we also prepared a carbon nanomaterial by using graphene-like carbon nano-fragments (CNFs) as a carbon building block for the anode of LIBs that can store a higher capacity than natural graphite [6,7].…”
Section: Introductionmentioning
confidence: 97%